2021
DOI: 10.1007/s11432-020-3010-6
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of polarimetric radar cross-section parameters for insect body width and length estimation

Abstract: Insect flight speed estimation analysis based on a full-polarization radar SCIENCE CHINA Information Sciences 61, 109306 (2018); Estimation of the power flux supplied by an electric arc to Ag-SnO 2 electrodes based on cross-section observations of the melted zone

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 25 publications
(39 reference statements)
0
6
0
Order By: Relevance
“…Weidong Li, Cheng Hu * , Senior Member, IEEE, Rui Wang, Muyang Li, Fan Zhang, Jiangtao Wang E of the radar properties of insects showed that use of these techniques can improve the accuracy of orientation measurements and mass estimates, enable body-length estimation, and discriminate between 'parallel' (PA) and 'perpendicular' (PE) insects (see below) [19][20][21] [22].…”
Section: Influence Of Non-horizontal Orientation On Measurement Of In...mentioning
confidence: 99%
“…Weidong Li, Cheng Hu * , Senior Member, IEEE, Rui Wang, Muyang Li, Fan Zhang, Jiangtao Wang E of the radar properties of insects showed that use of these techniques can improve the accuracy of orientation measurements and mass estimates, enable body-length estimation, and discriminate between 'parallel' (PA) and 'perpendicular' (PE) insects (see below) [19][20][21] [22].…”
Section: Influence Of Non-horizontal Orientation On Measurement Of In...mentioning
confidence: 99%
“…IoU = TP/(TP + FP + FN) (10) where TP (Ture Positive) and FN (False Negative) represent the number of positive pixels correctly classified and incorrectly classified respectively, and FP (False Positive) is the number of negative pixels classified incorrectly. For a segmentation task with a total of k + 1 classes (from L 0 to L k including background, in our task, k = 2), we assume that p ij is the number of pixels of class i inferred to belong to class j.…”
Section: Evaluation and Experimental Settingsmentioning
confidence: 99%
“…As an effective tool in studying animal migration patterns, they play an increasingly important role in protecting endangered species [9]. Insect radar can obtain the fine physical characteristics of flying animals [10] and is widely used in aerial biological monitoring. However, weather radar covers a wider area and can also effectively receive biological echoes in the scanning area, including birds [11], bats [12], and insects [13], so as to provide a reasonable explanation for a series of migration ecological problems [14].…”
Section: Introductionmentioning
confidence: 99%
“…The fully polarized entomological radar simultaneously transmits two polarized and waveform orthogonal signals, and obtains the target scattering matrix (SM) through the received H and V polarization echoes [11,12]. The SM contains all the information of the target under the current radar perspective, which can be used to calculate the orientation, mass and body length of insects [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%